The relationship between the variations in GÎ³ and AÎ³ promotors and the Hereditary Persistence of Fetal Hemoglobin (HPFH) - Aydin, Muhsin; Rencuzogullari, Eyyup; Dalyan, Ayse; Bayram, Suleyman; Genc, Ahmet (Cellular and Molecular Biology, 2018)
In the present study, sixty-two samples that have 1.5% and upper level of fetal hemoglobin (HbF), were examined to investigate the relationship between HbF level and non-deletional mutations in both GÎ³ (G gamma) globin (HBG2) and AÎ³ (A gamma) globin (HBG1) genes. Four variations were observed in the promotor of GÎ³ gene, which are -158C/T, -309A/G, -369C/G, and -567T/G. Also, four variations were observed in the 5’-UTR (untranslated regions) and promotor of AÎ³ gene, which are +25G/A, -369G/C, -499T/A, and -588G/A. One -222/-225 AGCA del homozygous and six variations as heterozygous in A gamma globin gene promotor region were also observed. The results of the current study suggested that there was a significant relationship between high HbF levels and two variations (-309A/T and -369C/G) in GÎ³ gene promotor. Additionally, a significant relationship between two variations (+25G/A and -499T/A) in AÎ³ gene promotor was also observed. Furthermore, the persons who carry these variations with high levels of HbF indicated that there might be a haplotype effect between these variations.